2011
DOI: 10.1136/jech.2010.117002
|View full text |Cite
|
Sign up to set email alerts
|

Stress, adherence to preventive measures for reducing influenza transmission and influenza-like illness

Abstract: Among students in the university setting, higher levels of perceived stress affect ILI symptom reporting but not compliance with preventive measures for reducing transmission of influenza. Further studies are needed to examine whether psychological stress is a key mechanism explaining socio-demographic health disparities in confirmed influenza infection among healthy persons in the community setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 38 publications
(35 reference statements)
1
15
0
Order By: Relevance
“…There may also be underlying demographic, socioeconomic, and employment-related factors contributing to differences in ILI prevalence [7], including job stress [28], [29], [30], [31], [32], job insecurity [33], availability of paid leave/benefits [34], and effort-reward imbalance (ERI) (which causes psychological distress that can negatively affect mental and physical health) [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There may also be underlying demographic, socioeconomic, and employment-related factors contributing to differences in ILI prevalence [7], including job stress [28], [29], [30], [31], [32], job insecurity [33], availability of paid leave/benefits [34], and effort-reward imbalance (ERI) (which causes psychological distress that can negatively affect mental and physical health) [35].…”
Section: Discussionmentioning
confidence: 99%
“…One study found that individuals classified as “high stress” experienced signficantly more episodes of URI and more days with URI symptoms than individuals classifed as low stress or intermediate [30]. A study of stress and adherence to preventive measure for influenza in university students found that while higher levels of percieved stress did not affect facemask or hand hygiene compliance, higher levels of stress were significantly associated with a 25% increase in ILI incidence [31]. Percieved stress has also been associated with higher ILI reporting [32].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the recent case report suggested that the severity of delusions may significantly increase in the context of the SARS-CoV-2 epidemic in patients with schizophrenia ( Fischer, Coogan, Faltraco, & Thome, 2020 ). However, there is some evidence that perceived stress does not hinder adherence to safety guidelines ( Perez, Uddin, Galea, Monto, & Aiello, 2012 ). At the same time, adherence to self-isolation measures may play a crucial role in slowing down the spread of SARS-CoV-2 (further on: coronavirus) infections, "flattening the curve" ( Kenyon, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The authors of this study argue that the results from nursing homes may provide clues to residential segregation's effects on seasonal influenza risk at the population level 24 . In a cohort study of U.S. college students, an increase in perceived stress score was associated with a 25% greater rate of self-reported ILI, after adjustment for demographic factors, behaviors and flu vaccination 23 .…”
Section: Seasonal Influenzamentioning
confidence: 97%
“…SES and exposure indicators utilized in these studies include percentage of households living in poverty 8,10-12 , female headed households 9,10 , household crowding 9,11 , and neighborhood population density 10 . Incidence: Two papers described disparities in rates of influenza susceptibility and exposure in older African Americans 24 and college students with higher perceived stress 23 . Black Americans in nursing homes were less likely to be vaccinated against seasonal influenza, and were less likely to have vaccinated contacts, due to racial and socioeconomic segregation in nursing home care.…”
Section: Seasonal Influenzamentioning
confidence: 99%